French Provincial Police and the Fall of the Second Republic : Social Fear and Counterrevolution - Forstenzer, Thomas R. (Book collections on Project MUSE., 1981)
While careful attention has been paid to the overthrow of the July Monarchy and to the subsequent development of radicalism under the Second Republic, little research has been done on the counterrevolutionary activity that preceded Louis Napoleon's seizure of power. Thomas Forstenzer revises the standard and current interpretations of social and political repression in France from 1848 to 1851. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.